Получение цементов в центробежно-ударной мельнице - Артамонов, А. В.; Кушка, В. Н.; Воробьев, В. В. (НТУ "ХПИ", 2007)
В статті розглядається обладнання, що володіє рядом переваг при подрібненні клінкера у порівнянні з кульовим млином. Наведені результати визначення будівельно-технічних властивостей цементу, отриманого в центробіжному млині МЦ при різних режимах його роботи.

The equipment, possessing a number of advantages of klinker grinding in comparison with a ball mill, is viewed in this article. There are the results of definition of cement property, produced at the centrifugal mill at different regimes of its work, in this article.
Keywords: строительные материалы; энергозатраты; помол; цементно-песчаные растворы; прочностные показатели; фракции